2021
DOI: 10.1037/xhp0000944
|View full text |Cite
|
Sign up to set email alerts
|

Thought dynamics under task demands: Evaluating the influence of task difficulty on unconstrained thought.

Abstract: As research on mind wandering has accelerated, the construct's defining features have expanded and researchers have begun to examine different dimensions of mind wandering. Recently, Christoff and colleagues have argued for the importance of investigating a hitherto neglected variety of mind wandering: "unconstrained thought," or, thought that is relatively unguided by executive-control processes. To date, with only a few studies investigating unconstrained thought, little is known about this intriguing type o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 64 publications
2
17
1
Order By: Relevance
“…Finally, for exploratory purposes, we examined the relation between rates of freely moving thoughts and performance (measured as d prime) on the 2-back task (see Figure 4). Consistent with recent research suggesting that freely moving thinking is resource demanding (Brosowsky et al, 2021), we found that participants who engaged in higher rates of freely moving thought tended to perform more poorly on the 2-back task, r = −.26, 95% CI [−.38, −.14], t (223) = −4.04, p < .001, with strong evidence favoring the alternative over the null, BF 10 = 338.86…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Finally, for exploratory purposes, we examined the relation between rates of freely moving thoughts and performance (measured as d prime) on the 2-back task (see Figure 4). Consistent with recent research suggesting that freely moving thinking is resource demanding (Brosowsky et al, 2021), we found that participants who engaged in higher rates of freely moving thought tended to perform more poorly on the 2-back task, r = −.26, 95% CI [−.38, −.14], t (223) = −4.04, p < .001, with strong evidence favoring the alternative over the null, BF 10 = 338.86…”
Section: Resultssupporting
confidence: 89%
“…We found no significant correlation between creativity ratings and level of flow, r = −.02, 95% CI [−.14, .10], t (272) = −.28, p = .777, BF 01 = 6.83, and no significant correlation between fluency and flow, r = .09, 95% CI [−.03, .21], t (272) = 1.50, p = .136, BF 01 = 2.38. Finally, we examined the relationship between flow-state responses following the n-back phase and proportion of freely moving thought (during the n-back) and found a significant positive association, r = .20, 95% CI [.08, .31], t (272) = 3.37, p = .001, BF 10 = 32.40, suggesting that flow and freely moving thoughts may reflect overlapping experiential states (see also Brosowsky et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not observe a difference in mind wandering propensity between the two task conditions, which is surprising given previous studies demonstrating an effect of task difficulty on mind wandering ( Seli, Konishi, et al. 2018 ; Brosowsky et al. 2021 ).…”
Section: Discussioncontrasting
confidence: 71%
“…Unconstrained thought/freely-moving thought has relatively low constraints (O'Neill et al, 2021). The frequency of participants' unconstrained thoughts has been found to be influenced by the difficulty of completing a task (Brosowsky et al, 2021) Although the dynamics of thought has been deeply theoretically discussed (Andrews-Hanna et al, 2020;Christoff et al, 2016;DuPre and Spreng, 2018) and somewhat empirically tested using behavioral paradigms (Li et al, 2021;O'Neill et al, 2021;Raffaelli et al, 2021;Sripada and Taxali, 2020), the neuroscientific substrates have not been reported. We told participants to relax and rest as much as possible without deliberately engaging in thinking and to let their minds move as freely as possible.…”
Section: Discussionmentioning
confidence: 99%